Clareamento caseiro com peróxido de hidrogênio 6%: eficácia, sensibilidade e impacto psicossocial em diferentes tempos de aplicação – ensaio clínico randomizado cego - (:unkn) unknown (Universidade Federal do Amazonas, 2021)
At-home bleaching is an effective clinical alternative in cases of patients who are at higher risk of tooth sensitivity, as this protocol uses smaller concentrations of Hydrogen Peroxide, applied daily for 1 hour. In order to evaluate the efficacy of athome bleaching, tooth sensitivity and the psychosocial impact associated with applications in time intervals of less than 1 hour, using 6% Hydrogen Peroxide, a randomized, blind, clinical trial was carried out with 15 minutes (PH15), 30 minutes (PH30), and 1 hour (PH60) application time groups. The sample size consisted of 90 patients, 30 for each intervention group. For this study, partial data from 63 patients were used. The at-home protocol was carried out for 14 days, and if the participants did not have satisfactory results at the end of this first stage, they would continue the bleaching until reaching treatment satisfaction. Color was evaluated by visual scales and spectrophotometer, tooth sensitivity by the Numerical Rating Scale (NRS) and Visual Analog Scale (VAS), and they were evaluated by the Psychosocial Impact of Dental Aesthetics Questionnaire (PIDAQ). As a result, all application groups showed clinical efficacy, with no difference between them (p0,05). For tooth sensitivity, an increase occurred gradually, getting higher as the application time got longer. Participants took an average of 23.4 days for satisfaction in the PH15 group, 30.9 days for the PH30, and 25.4 days for the PH60. PIDAQ had an overall positive change score. Data did not show statistical significance. With partial results, it was possible to observe a trend of the sample towards a similar effect between the groups regarding efficacy and total treatment time (approximately 4 weeks), incidence and intensity of tooth sensitivity are related to exposure time of the dental tissue to the bleaching agent, and 6%HP at home tooth bleaching has positive psychosocial impact for all groups.
6% hydrogen peroxide at home bleaching: efficacy, sensitivity and psychosocial impact at different application times – blind randomized clinical trial
Keywords: Dentes - Clareamento; Dentes - Clareamento - Tratamento alternativo; CIENCIAS DA SAUDE: ODONTOLOGIA: CLINICA ODONTOLOGICA; CIENCIAS DA SAUDE: ODONTOLOGIA: MATERIAIS ODONTOLOGICOS; Clareamento Dental; Eficácia; Impacto Psicossocial; Sensibilidade Dentária